INTERNAL BRANDING: ANTECEDENTS OF EMPLOYEE ATTITUDES, SATISFACTION, AND ORGANIZATIONAL LOYALTY - SCRIDON, Mircea-Andrei (Studia Universitatis Babeș-Bolyai Oeconomica, 2020)
As competition between employers has become more intense in recent years, employee-based differentiation has become one of the strategic solutions for many organizations. The objective of this paper is to test a nomological model between internal branding, attitude, satisfaction, and loyalty. Data were collected through a survey among employees of a leading electronics conglomerate from Romania. While the relationship between attitudes and loyalty is partially mediated by satisfaction, the relationship between internal branding and satisfaction is indirect, with full mediation by attitudes being detected. The results of the study agree with previous studies, which suggested that internal branding influenced certain employee behaviors, such as positive attitudes, satisfaction, or loyalty. JEL classification: M31, M52